Factors Influencing Basic Immunization Coverage in the Working Area of Puskesmas Dombusoi, Sigi Regency - Suwandi; Sudirman; Munawir H. Usman (PT. Anagata Sembagi Education, 2026)
The national achievement of Complete Basic Immunization (CBI) in 2024 only reached 83.09%, failing to meet the Strategic Plan (Renstra) target of 100%. This shortfall reflects real barriers in protecting children against Vaccine-Preventable Diseases (PD3I). This study aims to analyze the factors influencing the administration of basic immunization in the working area of UPT Puskesmas Dombusoi. A quantitative study using a cross-sectional design was conducted with 76 maternal respondents. Data were analyzed using bivariate chi-square tests and multivariate multiple logistic regression. The bivariate test detected significant effects of maternal knowledge ( ), maternal attitude ( ), location/distance ( ), and family support ( ) on immunization status. However, multivariate testing demonstrated that all variables lost their partial significance ( ) due to strong interactions and overlaps among the variables in the field. The study concludes that knowledge, attitude, geographical access, and family support contribute simultaneously as a unified determinant of child immunization status. Consequently, Puskesmas Dombusoi must reformulate its intervention strategies by combining persuasive Information, Education, and Communication (IEC) with the optimization of mobile health posts (posyandu keliling) in hard-to-reach areas to achieve national coverage targets.